2022
DOI: 10.11591/ijeecs.v28.i3.pp1286-1296
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of ferroresonance in the distribution zone by high ohmic reactor-shunt limiter

Abstract: Electrical network components catastrophically fail as a result of aberrant system oscillations. Also, consequently leads to saturation in the ferromagnetic core elements. These factors induce distortions in the voltage and current waveforms as well as a large rise in voltage or current. This paper presents the role of distributed generation (DG) in contributing to ferroresonance investigation reduction in the distribution sector. A high ohmic reactor-shunt limiter (HOR-SL) is introduced as a novel technique b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…This section implemented and compared the previously published mitigation methods with the proposed method. Therefore, the shunt resistance 36 , shunt reactor, nonlinear shunt reactor, series resistance, and RLC-SL were implemented, with each technique result indicated by a distinct color (shunt resistance was represented by black, shunt reactor was represented by yellow, series resistance was represented by red, nonlinear inductor was represented by green, and the proposed RLC-SL was represented by blue). While the results using ferroresonance mitigation techniques for the first and second load study cases are shown in Figs.…”
Section: Introductionmentioning
confidence: 99%
“…This section implemented and compared the previously published mitigation methods with the proposed method. Therefore, the shunt resistance 36 , shunt reactor, nonlinear shunt reactor, series resistance, and RLC-SL were implemented, with each technique result indicated by a distinct color (shunt resistance was represented by black, shunt reactor was represented by yellow, series resistance was represented by red, nonlinear inductor was represented by green, and the proposed RLC-SL was represented by blue). While the results using ferroresonance mitigation techniques for the first and second load study cases are shown in Figs.…”
Section: Introductionmentioning
confidence: 99%